Peer Perceptions of Students With Autism Spectrum Disorders. (September 2019) - Griffin, Whitney B.
This quasi-experimental study investigated behavioral intentions of 70 middle school participants toward engaging in activities with a student displaying characteristics of autism spectrum disorder (ASD) in a video vignette. Three video conditions were investigated: moderate to severe ASD, high-functioning ASD, and a typically developing control. Results of an analysis of variance indicated that participants reported significantly higher behavioral intentions toward the typically developing student and the student displaying more severe ASD symptomatology as compared to the student depicting high-functioning ASD. Participants were also able to differentially rate the behaviors they observed across the three conditions. These findings suggest that peers are capable of distinguishing among different behaviors typically displayed by students with ASD but may be less willing to socially engage with a student with mild or subtler characteristics. Implications regarding essential elements of interventions for peers based on the target student's level of functioning are discussed.